The Influence of Career Development and Organizational Commitment on Employee Performance - Ahmad Fadillah Maulana; Rizki Maulana Aditia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to analyze and determine the influence of career development and organizational commitment on employee performance at the Civil Service and Human Resources Development Agency of Cirebon district. This research uses quantitative methods and collects data from a sample of 84 employees using a survey questionnaire. The research results show that these three variables have a significant influence on employee performance. Therefore, the results of this study confirm the importance of these factors in improving overall employee performance. This shows that career development and organizational commitment play an important role in employee performance in government service.